Mutator Circuit for Memcapacitor Emulator Using Operational Transconductance Amplifiers - Mustafa Konal; Fırat Kacar (Elektronika ir Elektrotechnika)
In recent years, interest in memelements, including memcapacitors, has increased significantly following the realisation of memristors. This paper presents the design and implementation of a memcapacitor circuit based on operational transconductance amplifiers (OTAs). The proposed design is structured as a mutator circuit, where the second stage functions as a memristor, ultimately transforming the circuit into a memcapacitor emulator. The emulator features electronic tunability, which allows the charge value of the memcapacitor to be adjusted by modifying the capacitor in the mutator stage. The charge value of the memcapacitor can also be adjusted by varying the transconductance gm value of the OTA active element. Additionally, the operational frequency of the memcapacitor can be varied by altering the capacitor in the second stage. An adaptive learning circuit based on the memcapacitor emulator is demonstrated to validate the circuit performance. The time response obtained when a sine signal is applied to the memcapacitor circuit, the input voltage-charge relationship, and the charge-time response obtained when a square wave is used to demonstrate its memory characteristics are provided. All simulations were conducted using LTSpice with Taiwan Semiconductor Manufacturing Company (TSMC) 0.18 μm complementary metal oxide semiconductor (CMOS) process parameters. The results corroborate the effectiveness of the circuit, highlighting its potential for advanced electronic applications.